2014
DOI: 10.4103/1319-2442.132241
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic spectrum of crescentic glomerulonephritis: A hospital-based study

Abstract: Recent data regarding the clinical and histopathologic spectrum of crescentic glomerulonephritis (CSGN) among the Indian adult population is unknown. Our aim is to study the clinicopathological features and outcome of CSGN. It is a retrospective observational study from a tertiary care hospital in India over 3.5 years. Biopsy-proven cases of CSGN (i.e., >50% crescents in glomeruli) were included in the study. Cases with insufficient data were excluded. There were 34 cases of CSGN, accounting for an incidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 0 publications
2
21
0
1
Order By: Relevance
“…[9] Our study and earlier reports from India suggest that these patients are diagnosed late resulting in a poor renal outcome. [14] The poor response to therapy may be attributed to the presence of rapidly progressive glomerulonephritis in all our patients who were dialysis-dependent at the time of presentation. Alchi et al .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…[9] Our study and earlier reports from India suggest that these patients are diagnosed late resulting in a poor renal outcome. [14] The poor response to therapy may be attributed to the presence of rapidly progressive glomerulonephritis in all our patients who were dialysis-dependent at the time of presentation. Alchi et al .…”
Section: Discussionmentioning
confidence: 94%
“…[31011] An incidence of 6–16% has been reported from China and Japan. [12131415] Reports from India are variable. A study from North-East India including 34 patients of CrGN over a period of 3.5 years reported an incidence of 14.7%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the age distribution of patients was similar to previous studies, comparison with the existing series might have limitations in view of the different etiologic spectrum. [9][10][11] The histological parameters were comparable in the two groups except for the higher proportion of sclerosed glomeruli in ICGN. This might be secondary to the high proportion of patients with IgA nephropathy and lupus nephritis, which follows a more indolent course [12] .…”
Section: Resultsmentioning
confidence: 69%
“…The most common etiology of ICGN in the current study was IgA nephropathy followed by lupus and PIGN. A few studies from Asia have reported ICGN as the predominant etiology in adults [10][11][12][13] .…”
Section: Resultsmentioning
confidence: 99%